Design and Application of Storage and Inspection Integration Assembly Line for Distribution Automation Terminal based on RFID Technology. Issue 1 (1st February 2022) - Yin, Hui; Gu, Lingyun; Chen, Jie; Wang, Haibo; Che, Wei; Xin, Qian
Abstract: Acoording to the needs of large-scale power distribution equipment testing and quality control, a storage and inspection integrated pipeline management and control system based on radio frequency identification technology has been constructed. The overall design ideas, key functions and business processes of the system are described, and implementation methods are introduced in detail. After pilot application, the system completed the real-time update of the whole process quality inspection data information, such as the test progress, detection data, and storage status, which improved the detection efficiency and management cost, greatly reduced the manpower input, and realized integrated management and pipeline inspection of internal resource.